Design of Automatic Security System Based Internet of Things at the Museum - Yuwana, Rahmat Ageng; Fajaryati, Nuryake; Jie, Ferry (Elinvo (Electronics, Informatics, and Vocational Education), 2024)
This research aims to determine the procedures for developing an Internet of Things (IoT)-based Automatic Security System as a security device for museum objects and to test its feasibility based on user feedback in museums. The Design Thinking model used consists of five stages: Empathize (understanding the user's perspective), Define (gathering information on the encountered problems), Ideate (generating innovative ideas), Prototype (creating a prototype of the obtained ideas, ensuring the functionality of each device feature, and validating the product through expert judgment for feedback and product revision), and Testing (evaluating the system's feasibility using Usability standards based on ISO/IEC 9241-11, focusing on Effectiveness, Efficiency, and Satisfaction with user involvement). The research results indicate that the IoT-based Automatic Security System has met optimal outcomes based on Usability aspects, namely: the Effectiveness analysis showed a ratio above 100% with a Very Effective level of achievement; the Efficiency aspect analysis received user feedback with a device usage rate of 1.35 goals per second; and the Satisfaction analysis, using the System Usability Scale (SUS) questionnaire, scored 78.25, indicating an Excellent level, suggesting that the system is worthy of use.